Modeling and Simulation of Solar Photovoltaic Renewable Energy Sources Power Generation System for MGs and Loss of Mains Detection - Ong’ondo, Mogaka L.; Nyauma, Nyakoe G.; Saulo, Michael Juma (Multidisciplinary Journal of Technical University of Mombasa, 2020)
Power generation from Renewable Energy Sources (RESs) is steadily increasing due to a number of reasons. These include government subsidies on these RESs, improvement in technology in their manufacture and efforts to reduce greenhouse gas emissions. However, these RESs have associated challenges like intermittency in power generation hence unreliable power supply. Solar PV is gaining popularity as compared to other RESs due to its unique advantages in grid connected applications. It is therefore important to carry out accurate design and enough simulations on its dynamic behavior before actual installation at any given location using local environmental parameters. This paper discusses the detailed modelling, simulation and dynamic behavior of solar PV power generation systems for MG applications using Matlab/Simulink platform.